Estudio de la composición bioquímica del camarón Litopenaeus Vannamei, sostenida bajo condiciones de alimentación natural y artificial. - Espinosa Aguilar, Cecilia P. (2005)
This research tas kwas carried out in the Laboratorio de Bromatología de la Facultad de Ciencias Químicas de la Universidad Técnica de Machala and the Laboratorio de Calidad de Agua de la Camaronera Mariluna. The purpose of the investigation was to find out the biochemical composition and energetic contents of shrimp.